1985
DOI: 10.1002/1097-4679(198511)41:6<851::aid-jclp2270410621>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemical dependence and clinical Depression in pregnancy

Abstract: The Short Form of the Beck Depression Inventory (BDI) was administered to 54 chemically dependent pregnant women to assess the extent and depth of depression in the population. The women were divided into three groups by age: Teenagers, young adults, and older adults. Results suggested that this population, as a whole, scored very high on this depression scale. Further, results indicated that the older chemically dependent women scored significantly higher on the depression index than did either of the two you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 13 publications
1
13
1
1
Order By: Relevance
“…Substance abuse among pregnant women remains a particular concern, with approximately 1.9% of pregnant women reporting binge alcohol use (Centers for Disease Control [CDC] 2004) and 3.7% reporting drug use during the previous month on population-based surveys (SAM-HSA 2002). Studies have reported a high incidence of cooccurring mental health disorders among substance abusing pregnant women, including overall psychological distress (Miles et al 2001) and depressive symptoms (Burns et al 1985;Marcenko and Spence 1995). The burden of depression coupled with substance abuse makes the treatment prognosis worse than for either problem alone (Bobo et al 1998;Greenfield et al 1998;Driessen et al 2001).…”
Section: Introductionsupporting
confidence: 75%
“…Substance abuse among pregnant women remains a particular concern, with approximately 1.9% of pregnant women reporting binge alcohol use (Centers for Disease Control [CDC] 2004) and 3.7% reporting drug use during the previous month on population-based surveys (SAM-HSA 2002). Studies have reported a high incidence of cooccurring mental health disorders among substance abusing pregnant women, including overall psychological distress (Miles et al 2001) and depressive symptoms (Burns et al 1985;Marcenko and Spence 1995). The burden of depression coupled with substance abuse makes the treatment prognosis worse than for either problem alone (Bobo et al 1998;Greenfield et al 1998;Driessen et al 2001).…”
Section: Introductionsupporting
confidence: 75%
“…This rate is comparable to the general substance abuse population; however, it is much higher than rates of Axis I disorders in the general population. Depression is especially prevalent (56%) in drug-dependent pregnant populations (Burns, Melamed, Burns, Chasnoff, & Hatcher, 1985;Regan, Leifer, Matteucci, & Finnegan, 1982). The assessment of depression is important in substance-abusing pregnant women because it can negatively impact treatment outcomes, as shown in samples of cocaine-using pregnant women (Haller, Miles, & Dawson, 2002;Ingersoll, Lu, & Haller, 1995), and contribute to adverse maternal outcomes (Regan, Rudrandff, & Finnegan, 1980).…”
Section: Co-occurring Disorders Pregnancy and Substance Use Disorderscontrasting
confidence: 60%
“…There is a high prevalence (56%-73%) of co-occurring Axis I disorders in drug-dependent pregnant women (Burns, Melamed, Burns, Chasnoff, & Hatcher, 1985;Fitzsimons, Tuten, Vaidya, & Jones, 2007;Haller et al, 1993;Regan, Leifer, Matteucci, & Finnegan, 1982). Mood disorders during pregnancy have been associated with adverse maternal health behaviors, a high risk of postpartum depression, and behavioral effects on the offspring (Bonari et al, 2004;Cohen, Nonacs, Viguera, & Reminick, 2004).…”
Section: Managing Co-occurring Psychiatric Disordersmentioning
confidence: 99%